2020
DOI: 10.21153/jtlge2020vol11no1art898
|View full text |Cite
|
Sign up to set email alerts
|

Ignorance is risk: An exploratory investigation of students’ perceptions of their education–employment pathways

Abstract: The widely held view that higher education constitutes a gateway to employment has underpinned the dramatic widening of access to university in recent decades. However, globalisation and technological development have complicated the task of enhancing the employability of students, as the future world of work has become ever-more dynamic and unpredictable. Given such conditions, the delivery of employability teaching has become a central focus of many higher education providers (HEPs). To meet their responsibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Views have shifted from obtaining satisfying work to the adaptive capacity an individual need for obtaining and retaining work during an environment of fast-moving changes (De Vos et al 2021;Presti et al 2019). The later conceptualisation includes the need to strengthen self-awareness, self-efficacy, proactivity, career building skills, self-directedness, resilience, adaptability, agility, reflectivity, persistence/grit, social and cultural awareness, emotional intelligence, lifelong learning, growth mindset, and understanding of the labour market, as some of the bedrocks for a sustainable career in precarious, continuously evolving, and turbulent labour markets of the 21st century (Rowe 2019;Van Harten et al 2022;Masole and van Dyk 2016;Lock and Kelly 2020). What is clear is that employability skills are highly sort after by most employers when recruiting entry-level graduates (Robinson and Garton 2008;Lim et al 2016;Succi and Canovi 2020).…”
Section: Employability Skillsmentioning
confidence: 99%
See 3 more Smart Citations
“…Views have shifted from obtaining satisfying work to the adaptive capacity an individual need for obtaining and retaining work during an environment of fast-moving changes (De Vos et al 2021;Presti et al 2019). The later conceptualisation includes the need to strengthen self-awareness, self-efficacy, proactivity, career building skills, self-directedness, resilience, adaptability, agility, reflectivity, persistence/grit, social and cultural awareness, emotional intelligence, lifelong learning, growth mindset, and understanding of the labour market, as some of the bedrocks for a sustainable career in precarious, continuously evolving, and turbulent labour markets of the 21st century (Rowe 2019;Van Harten et al 2022;Masole and van Dyk 2016;Lock and Kelly 2020). What is clear is that employability skills are highly sort after by most employers when recruiting entry-level graduates (Robinson and Garton 2008;Lim et al 2016;Succi and Canovi 2020).…”
Section: Employability Skillsmentioning
confidence: 99%
“…A study in the Czech Republic found that university studies were theory-based and detached from practice (Gawrycka et al 2020). Lock and Kelly (2020) observed that some Australian students often have limited understanding of how different courses they undertake at university are linked to their chosen careers. Many students have a "poor understanding of the education-employment pathways on which they have embarked" (Lock and Kelly 2020, p. 22).…”
Section: Students' Responsibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In this workshop, students get acquainted with industry leaders and peers to gain useful insights for working in the real world, exchanging views and visiting real workplaces (Lock & Kelly, 2020). This example shows the importance of universities incorporating entrepreneurship into the curriculum to enable their graduates to better fit the current concepts of employability (Azmi, et al, 2018).…”
Section: Theoretical Foundationsmentioning
confidence: 99%